THERMAL EFFECTIVENESS OF THE GAS FLOW VORTICAL HEAT-RELEASE INTENSIFICATION AT AXIAL AND TRANSVERSAL FLOWING-AROUND THE ROUND-TUBULAR SURFACES. Part 1 - V. B. Kuntysh; A. V. Sukhotskiy; A. V. Yatsevich (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The authors present a numerical comparison of the thermal effectiveness of the monophasic-stream axial flowing inside a smooth pipe with transversal flow-around of staggered and in-line tube banks in interval Re = (3−500) × 103 with equal power input N0 = idem for priming gas (air) flow. Coefficient estimates the thermal effectiveness quantitatively and represents the relation of heat-emission coefficients of surface i being examined to basesurface k assumed standard. The paper offers estimation formulae for the specific power input N0 at axial and transverse flowing-around of the tubular surface and shows an accounting technique for the stream-pressure local losses. To exclude the heat-exchange surface square influence on the result and for obtaining the comparable valuesi it is indispensable to calculate the power input by the effective value of the surface square.While performing computations of the energy effectiveness it is necessary to recon with the fact that accounting for the stream-pressure local losses at the tube entrance and exit reduces the axial-stream thermal effectiveness coefficient by 33 %. Transverse flow-around of the smooth tube banks is more efficient in comparison with the in-tube axial flow within the entire interval of numeral Re changing. The staggered banks thermal effectiveness at N0 = idem is by 10−13 % more than of the in-line ones. In transient interval Re = (3−10) × 103 at N0 = idem the staggered-bank heat-emission coefficient with outside flow-around exceeds the heat-emission with in-tube air flow by 5−2,1 times, and at Re = 105 – by 1,6 times.